Ferdinand de Saussure on the Affinities Between Economics and Semiotics - Nöth, Winfried (Recherches sémiotiques / Semiotic Inquiry, 2020)
The paper reconstructs, from the manuscripts of the Course in General Linguistics, Saussure’s reflections on the affinities and differences between linguistics and economics, particularly his model of commodities as signs and elements of the economic system, analogous to the verbal sign as a basic unit of the language system. Key notions of this comparison are signifies vs. signifieds arbitrariness, syntagmatic and paradigmatic association, positive vs. negative value, type and token, substance and form. The paper studies how H. Lefebvre, J. Baudrillard, Rossi-Landi, and the cultural anthropologists M. Sahlins, M. Douglas, and B, Isherwood apply elements of this model in analyses of goods and commodities. The paper argues that Saussure proposes a weak analogy, that one of its weaknesses is the comparison at the level of the word instead of the one of a proposition or an argument. It concludes with the affirmation that Saussure’s analogies have a great heuristic value for cultural semiotics.